Prevalence of syphilis, neurosyphilis and associated factors in a cross-sectional analysis of HIV infected patients attending Bugando Medical Centre, Mwanza, Tanzania - Adeodatus Haule; Betrand Msemwa; Evarista Mgaya; Peter Masikini; Samuel Kalluvya (BMC, 2020)
Abstract Background HIV-syphilis co-infection can enhance the rapid progression of early or late latent syphilis to neurosyphilis and can cause catastrophic neurological complications. In studies in Mwanza, syphilis affects ~ 8% of healthy outpatients and studies done in the 1990s have suggested that up to 23.5% of HIV-syphilis co-infected patients also have neurosyphilis. Methodology This was a cross sectional study in which adult HIV infected patients who were hospitalized or attending the outpatient Care and Treatment Clinic (CTC) were interviewed using a structured questionnaire and screened for syphilis using serum Treponema Pallidum Hemagglutination Assay (TPHA). Blood was also taken for CD4+ T cells and viral load. Those who were found to have syphilis underwent neurological examination for any neurologic deficit and were offered a lumbar puncture. Results The prevalence of syphilis in HIV infected patients was found to be 9.6%. The majority of patients were female (72.5%) and median age was 42 years [interquartile range, 32-50]. Most patients were on ART (99.4%). In the study population of 1748 participants, 9.6% were TPHA positive; the majority (89.2%) reported not knowing their syphilis status and not previously been treated. One hundred and forty-one participants with syphilis had neurological examinations performed. Four of these had abnormal findings that necessitated a lumbar puncture. Neurosyphilis was confirmed in one patient (0.7%). Conclusion The high prevalence of syphilis in HIV infected patients indicates that there is a need to increase efforts in targeting this population to reduce sexually transmitted infections. Screening for syphilis should be done for all HIV patients given the high prevalence of the infection and the risk that aggressive forms of neurosyphilis can occur despite recovery of CD4+ T cell counts in untreated syphilis.